Una experiencia pedagógica en la enseñanza del inglés con fines específicos dentro del currículo universitario: caso de la carrera de Ingeniería Eléctrica, Universidad de Costa Rica, Sede del Pacífico - Quesada Chaves, María José (2019)
Today's society demands that new generations of professionals can be trained in the mastery of a language additional to their mother tongue, so this study implies the need to implement the English language within the university curriculum to promote an integral academic task that allows students to receive linguistic tools and expand the development of their communicative competence favoring their inclusion in the job market after finishing their undergraduate and graduate studies. Then, the mixed method of research was used, and a survey was applied to the first-year students of the Electrical Engineering career of the University of Costa Rica, in the Pacific Campus; after completing an English course for specific purposes during a semester; likewise, when analyzing the information collected, quantitative data of the participating population were included and at the same time a description of the demands presented by the job context in which the population involved will be incorporated. Therefore, within the main findings it is analyzed that the University of Costa Rica has an approximate of 340 academic offers but only 48 of them include language courses within their curriculum, and just 2 majors in particular specify English courses for specific purposes. Thus, it is concluded that there is a need to include English courses for specific purposes within the university curriculum, especially in engineering to provide to student with better tools for practical use within the demands of modern professional skills.